Analisis Adopsi Sistem ERP dalam Mengoptimasi Industri Pangan Menggunakan SEM dan Model UTAUT2 - Haryasena Panduwiyasa; Rachdian Habi Yahya (Jurnal Sistem Informasi Bisnis, 2023)
In the era of Society 5.0 and the post-COVID-19 recession, entrepreneurs experienced digital disruption and economic instability, especially in the food industry sector. The low awareness of entrepreneurs in adopting technology and information systems, as well as their doubts about the high cost and time that needs to be allocated, are also reasons why the process of adopting technology and information systems is increasingly difficult to realize. To overcome costs and a relatively long development process, one of the efforts that companies can make is to adopt an open-source Enterprise Resource Planning (ERP) system that is useful for supporting resource management and decision-making. The purpose of this research is to prove how the adoption of ERP systems can support business digitalization processes and can produce industrial systems that are agile, effective and efficient. A series of analyzes were carried out using a survey aimed at 292 food industry business actors who had been digitalized by ERP, to prove the influence of behavioural factors on ERP usage using the UTAUT2 model, with the variables tested including performance expectations (PE), effort expectations (EE), price values (PV), facility conditions (FC), habits (HT), and behavioural intention (BI) toward the use behaviour of ERP (UB) in the food industry sector in Central Java, Indonesia.